On the inverse eigenvalue problems for a Jacobi matrix with mixed given data - Nizhnik, L. P. (Methods of Functional Analysis and Topology, 2018)
We give necessary and sufficient conditions for existence and uniqueness of a solution to inverse eigenvalues problems for Jacobi matrix with given mixed initial data. We also propose effective algorithms for solving these problems.